ANALISIS KOMPUTASI PENDAPATAN BREAK EVEN POINT (BEP) DAN R/C RATIO PETERNAKAN AYAM PETELUR RENCANG GESANG FARM DI DESA JANGGLENG KECAMATAN KALORAN KABUPATEN TEMANGGUNG - Rinto Rinto; Siswanto Imam Santoso; Rina Muryani (MEDIAGRO, 2017)
This study aims to determine the value of Break Even Point (BEP), the value of R/C  Ratio and counting Computing revenues in poultry Rencang Gesang Farm Polutry. The research was conducted on January 18, 2016 - February 22, 2016 in the village of Janggleng, Kaloran District, Temanggung District, Central Java. This study uses the case study method. The collection of data used in the study was done by  direct interview and observation. These data consist of primary data and secondary data. Primary data were obtained by direct interviews with respondents, managers and workers of companies which are based on a questionnaire. Secondary data were obtained from the accounting records at the Rencang Gesang Farm Polutry Farm for 36 months (2013-2015), which includes the cost of feed, labor costs, egg production and the selling price of eggs. In addition, secondary data obtained from departments or agencies associated with this research. The conclusion of this study showed that the level of profitability in the poultry farm Rencang Gesang Polutry Farm for 3 years (2013-2015), namely 26.97%, 14.65% and 14.29%. Value Break Even Point (BEP) units a year (2013-2015), namely 55 099 kg, 56 979 kg and 52 825 kg while the value of the break even point to prices in (2013-2015) is Rp 2,299,611,164, Rp 3,207,697,510 and Rp 3,452,146,815. Rated R/C Ratio Rencang Gesang Farm Polutry profitable because the value of R/C Ratio is more than 1. Keywords: Break Even Point (BEP), R/C Ratio, Laying Hens.